The natural course of bulimia nervosa and binge eating disorder in young women. - Fairburn, C; Cooper, Z; Doll, H; Norman, P; O'Connor, M (2000)
BACKGROUND: Little is known about the relative course and outcome of bulimia nervosa and binge eating disorder. METHODS: Two community-based cohorts were studied prospectively over a 5-year year period. One comprised 102 participants with bulimia nervosa and the other 48 participants with binge eating disorder (21% [9/42] of whom had comorbid obesity). All participants were female and aged between 16 and 35 years at recruitment. The assessments were at 15-month intervals and addressed eating disorder features, general psychiatric symptoms, and social functioning. RESULTS: Both cohorts showed marked initial improvement followed by gradual improvement thereafter. Between half and two thirds of the bulimia nervosa cohort had some form of eating disorder of clinical severity at each assessment point, although only a minority continued to meet diagnostic criteria for bulimia nervosa. Each year about a third remitted and a third relapsed. The outcome of the binge eating disorder cohort was better, with the proportion with any form of clinical eating disorder declining to 18% (7 of 40) by the 5-year follow-up. The relapse rate was low among this cohort. There was little movement of participants across the 2 diagnostic categories and few sought treatment. Both groups gained weight, with 39% of the binge eating disorder cohort (14 of 36) meeting criteria for obesity at 5-year follow-up. CONCLUSIONS: These findings suggest that, among young women in the community, bulimia nervosa and binge eating disorder have a different course and outcome. Whereas the prognosis of those with bulimia nervosa was relatively poor, the great majority of those with binge eating disorder recovered.